Multiplication modules and principal elements of modules over noncommutative rings - Sevim, Esra Sengelen, (Utilitas Mathematica, 2012)
By considering the notion of multiplication modules over a noncommutative ring with identity, first we introduce the notion of the product of two submodules of such modules. Then we use this notion to characterize the prime submodules of a multiplication module. Moreover we define some principal elements of modules over a noncommutative ring and we prove theorems related to principal elements.